Study on the Chinese Subfamily Anostostomatinae (Orthoptera: Anostostomatidae) IV: One new recorded species Anabropsis (Apteranabropsis) tonkinensis Rehn, 1906 - Lu, Xiangyi; Liu, Jing; Bian, Xun (Zootaxa, 2022)
This paper is the fourth study of the subfamily Anostostomatinae from China and reports one newly recorded species, Anabropsis (Apteranabropsis) tonkinensis Rehn, 1906. Also, we reported the mitochondrial genome and inferred the phylogenic relationship among the genus Anabropsis based on two specimens. Two complete mitogenomes were 16059 and 16052 bp in size and consisted of 37 genes and a control region. The overall base composition exhibited a clear AT bias. Most protein-coding genes started with the codon ATN and ended with typical stop codons TAA. The phylogenetic analyses based on mitogenomes and several morphological characteristics provided meaningful genetic information for Anabropsis and validated the phylogenetic relationships among the subgenera.